A new one-step iterative process for approximating common fixed points of a countable family of quasi-nonexpansive multi-valued mappings in CAT(0) spaces - Suthep Suantai (2018)
© 2017 Iranian Mathematical Society. In this paper, we propose a new one-step iterative process for a countable family of quasi-nonexpansive multi-valued mappings in a CAT(0) space. We also prove strong and Delta-convergence theorems of the proposed iterative process under some control conditions. Our main results extend and generalize many results in the literature.